PENGARUH STRUKTUR MODAL, KINERJA KEUANGAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Suparman Suparman (JMB : Jurnal Manajemen dan Bisnis, 2020)
The purpose of this study was to examine the effect of capital structure, corporate financial performance, company growth, company size on firm value in banking companies on the Indonesia Stock Exchange. The population in this study were all banking companies listed on the Indonesia Stock Exchange with the research period from 2011 to 2015, totaling 14 banking companies. The data used are secondary data. The sample selected using Purpose sampling amounted to 9 companies. The results of this study indicate that partially the capital structure variable has a positive and significant effect on firm value, financial performance variables have a positive and significant effect on firm value, growth variables have a positive and insignificant effect on firm value and size variables have a positive and insignificant effect on firm value. , And simultaneously the capital structure, company financial performance, company growth and company size have an influence on the value of banking companies listed on the Indonesia Stock Exchange in the period 2011 to 2015.